An investigation of the merkle signature scheme (MSS) for cryptographically generated address (CGA) signatures in mobile IPv6 - Qadir, Sana; Siddiqi, Mohammad Umar; Al-Khateeb, Wajdi Fawzi Mohammed (International Journal of Network Security, 2014)
Cryptographically Generated Address (CGA) Signatures are a promising feature of Mobile IPv6 (MIPv6) and are slowly being considered suitable for signing the Binding Update (BU) message. However, the use of the Rivest- Shamir-Adleman (RSA) by the CGA signature algorithms is considered to be a very serious limitation. This is be- cause RSA provides only limited computational security and incurs significant performance overhead. This work investigates the use of an alternative signature scheme called Merkle Signature Scheme (MSS) for use in the CGA signature algorithms. The results show that compared to RSA, MSS provides stronger computational security and significantly improves the performance of the key genera- tion and the CGA signature generation operations.